PENGARUH WORK LIFE BALANCE IKLIM ORGANISASI DAN REWARD MASA PANDEMI TERHADAP KEPUASAN KERJA - M. Ramadhoni Azdanal; Fakhry Zamzam; Neny Rostiati (Program Magister Manajemen Indo Global Mandiri University, 2021)
The purpose of this study was to determine the Effect of Work Life Balance Organizational Climate and Rewards during the Covid 19 Pandemic on Job Satisfaction of PT BNI (Persero) Tbk KCU Palembang employees partially or simultaneously. This research method uses descriptive and verification surveys, field data collection uses questionnaires, interviews and documentation techniques. This research is an associative research, where in this study there are variables that are related and can influence other variables. The population of this study were 78 employees of PT BNI (Persero) Tbk KCU Palembang. Data processing using SPSS 25 analysis tool.The results of the study show that Work Life Balance affects job satisfaction, organizational climate affects job satisfaction, rewards affect job satisfaction, work life balance, organizational climate and rewards during the pandemic affect job satisfaction simultaneously.